Sāmānyaniruktiprakaraṇam - Gaṅgeśa, 13th cent (Kāśīsaṃskrtasīrījapustakamālā ; Nyāyavibhāga, 1938)
Commentary, with Gaṅgā supercommentary on portion of Tattvacintāmaṇi of Gaṅgeśa, dealing with the definition of fallacious middle term Hetvābhāsa.